Mineral-specific Quantitative Element Mapping Applied to Visualization of Geochemical Variation in Glauconitic Clasts - Keulen, Nynke; Weibel, Rikke; Malkki, Sebastian N. (Frontiers in Earth Science, 2022)
The geochemical composition of glauconitic clasts is a provenance marker to distinguish the origin of gravity flows in sedimentary basins. Their geochemical variation is visible in major and trace elements composition, where the former can be visualized by element mapping of glauconitic clasts. By applying automated quantitative mineralogy on a Scanning Electron Microscope equipped with the ZEISS Mineralogic™ software platform, we developed a new way to visualize the element distribution in selected minerals, while masking out the other minerals simultaneously. This software applies energy dispersive spectroscopy spectrum deconvolution for each analysis point, therefore quantitative concentrations (wt%) of each element are determined for each pixel and visualized in the false-coloured element map with reproducible results for individual grains and zonations in these grains. The investigated glauconitic clasts were collected from eleven drill cores, covering a 1400m-depth interval, and crosscutting four different gravity flow members. The clasts show three different trends: first, cores of glauconitic clasts show a variation of compositions that are mainly dependent on the conditions during their formation. This is most visible for Si and Al. Secondly, the composition of the glauconitic clasts changes with depth, their cores become more Fe-rich and K-poor. This is probably an alteration effect, depending on temperature, and therefore mineral stability. And, thirdly, most glauconitic clasts are zoned, where rims are richer in Al and poorer in Fe and K. The visualization of the chemical variation in the glauconitic clasts proofs to be a useful tool to separate these conflicting element exchange processes.